2013
DOI: 10.1007/s00264-013-1845-1
|View full text |Cite
|
Sign up to set email alerts
|

The study of broken quadrilateral surface in fractures of the acetabulum

Abstract: Purpose Three-dimensional computerised tomography (3DCT) can provide comprehensive patho-anatomy of complex bone on a single image. Though important, the key articular quadrilateral [Q] surface has not been a part of the systems developed for classifying acetabulum fractures. The purpose of the study was to simplify the complexity of classification by the direct sign of the broken Q surface which lies opposite the entire floor of the acetabulum. Methods The study reviewed 84 acetabular fractures using 3DCT ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…We have in this study there were males 75.5% and females 24.5%;Gänsslen et al( 16) Zinghi et al [17] found similar results as they reported that the majority of patients were men. There were 28.5% fell from height and 71.4 % had car accidents; Parasartritha and Chaivanichsiri [18] reported 14.7 % fell down and 85.3 % due to Road Traffic Accident (RTA) in their study however their associated injuries were higher as they were reported 60.3 % associated injuries. Gänsslen et al [16] and Praveen et al, [19] had similar data to our study as they reported 78.9 % RTA and 21.1 % fell from heights, and associated injuries in 57.9 % of their series.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We have in this study there were males 75.5% and females 24.5%;Gänsslen et al( 16) Zinghi et al [17] found similar results as they reported that the majority of patients were men. There were 28.5% fell from height and 71.4 % had car accidents; Parasartritha and Chaivanichsiri [18] reported 14.7 % fell down and 85.3 % due to Road Traffic Accident (RTA) in their study however their associated injuries were higher as they were reported 60.3 % associated injuries. Gänsslen et al [16] and Praveen et al, [19] had similar data to our study as they reported 78.9 % RTA and 21.1 % fell from heights, and associated injuries in 57.9 % of their series.…”
Section: Discussionmentioning
confidence: 86%
“…According to Modified Merle d' Aubigne score [8], Stability score were ranged from (5-6) with mean score 5.9 SD± 0.2; pain score ranged from (3-6) with mean 5.7 SD±0.6 and ability to walk score ranged from2-6 with mean score 5.6 SD±0.5. The final results mean score 17.2 SD±1.2 and ranged from [11,18] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Most should agree that anatomic reduction of weight bearing surface and concentric reduction of the hip joint is essential for long-term satisfactory results [2]. The type and nature of the acetabular fracture substantially influence which approach is used [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that inexperienced readers have an accuracy of only 11% when diagnosing these fractures on the basis of radiographs, a percentage that is no greater than the hazard ratio 6 , 7 , and that general orthopaedists and senior orthopaedic residents have an accuracy of <65% 7 , 8 . Considering these results, some authors have tried to simplify the analysis of acetabular fractures by offering new classification systems or diagnostic algorithms 9 - 13 . Some authors have introduced relatively complex redefinitions of acetabular landmarks that do not result in a real clarification of the Letournel classification 9 , 10 .…”
mentioning
confidence: 99%
“…Considering these results, some authors have tried to simplify the analysis of acetabular fractures by offering new classification systems or diagnostic algorithms 9 - 13 . Some authors have introduced relatively complex redefinitions of acetabular landmarks that do not result in a real clarification of the Letournel classification 9 , 10 . Other authors have opted for the development of a new classification system involving 3 main categories with subcategories 11 , 13 .…”
mentioning
confidence: 99%